Sistem Proteksi Thermal Overload Relay (TOR) pada Motor Induksi 3 Phasa sebagai Penghancur Batu Bara di PT. Mitrabara Adiperdana Tbk - Sartika, Linda; Prasetia, Abdul Muis; Krisnawati, Mega (Majalah Ilmiah Teknologi Elektro, 2025)
During operation, the induction motor used as a coal crusher may experience excessive workload, leading to potential overheating and system trips that disrupt the production process. To mitigate such issues, a reliable system is required to limit or prevent operational disturbances. This research collected data on the induction motor protection system at PT Mitrabara Adiperdana Tbk, followed by calculations of relay settings, specifically Over Current (OC) settings, which were then compared with observed field data. The findings indicate a significant discrepancy between the Time Overcurrent Relay (TOR) settings observed in the field and the calculated TOR settings based on motor current performance data from January and February 2023. This discrepancy arises from the operational shift of the crusher motor, which initially functioned as the primary crusher and later served as a backup. As a primary crusher, the motor operated at higher power and current levels, reaching 35 A. However, after transitioning to a backup role, the motor's performance declined, with the current reducing to 9.9 A. Similarly, power output varied monthly, with the highest recorded in January at 9.91 kW, decreasing to 9.05 kW in February. These changes in motor performance, particularly reduced current and power, significantly influenced the calculated TOR settings.